MANAJEMEN BISNIS DAN PEMASARAN BUDIDAYA BURUNG “LOVEBIRD” DI INDONESIA - Munawir Munawir (Equilibrium Point : Jurnal Manajemen dan Bisnis, 2019)
The origin of lovebird from the African continent, there are about 25 species with a very attractive color, kept for pleasure, for hobbies, the price is quite high / expensive, has spread to various countries including Indonesia, cultivated including bredding and traded.Maintenance / cultivated of lovebird aims to obtain a lot of children’s offspring children and do bredding / crossed in order to obtain superior offspring in color, sound, movement / action and others, so that if sold can be obtained the sale value (money) is high.Result of case study research on lovebird breeder on Jl. Langgar, RT 04/01 Cipadu, Larangan, Tangerang City obtained the result : R/C = 1,75 which means that the lovebird business is feasible and profits of Rp. 68.670.000,- / year or for Rp. 5.722.000,- / month ( here wage / labor fee has been calculated as much as 2 people).